SOSIALISASI PROGRAM PENGELOLAAN SAMPAH MENJADI ECOBRIK DI PENDIDIKAN DASAR DESA WOTGALIH, LUMAJANG - Rukmana, Sarah Nurmala Putri; Rahmasari, Ayu; Putri, Vadila Mulia; Agustia Putri, Elsa Sabrina; Setyowati, Laras; Al Farabi, Akhfad; Dhohan, Ajie; Wahyu Ramadani, Tasya; Edo Wahyudi, Kalvin (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
Garbage is one of the problems in Indonesia that can have a negative impact on the environment and public health. Environmental cleanliness is a shared responsibility, including children such as children who are still sitting in elementary education. It is necessary to give understanding and habituation from an early age so that they can become individuals who can maintain environmental cleanliness, starting from building the habit of disposing of waste in its place to being able to reuse waste that can still be used/reprocessed. Ecobricks are plastic bottles filled densely with non-biological waste, namely plastic. Ecobricks are a grassroots solution to plastic waste. Community service activities carried out by students of the Thematic KKN Disaster Resilient Village UPN Veterans East Java group 123 in Wotgalih Village, Yosowilangun District, Lumajang Regency involved students to process ecobrick waste. This community service uses a qualitative approach to the observation method. Collecting data through direct observation, participatory-observation, interviews and door prize distribution.